COPD in females- Seeing through the smoke - S R Sreedevi; Ramesh Holla; A. K Vishak; Bhaskaran Unnikrishnan; T Rekha; P Prasanna Mithra; Nithin Kumar; Mithun Rao (Lung India)
Chronic obstructive pulmonary disease (COPD) is a type of lung disease marked by permanent damage to tissues in the lungs. Over time, chronic obstructive pulmonary disease (COPD) can make breathing difficult due to permanent lung damage. COPD encompasses two main conditions chronic bronchitis, where inflammation and scarring narrow the large airways, and emphysema, where the tiny air sacs in the lungs are damaged. The widespread lung condition, chronic obstructive pulmonary disease (COPD), is largely preventable and treatable, affecting people of all genders globally. There are many studies estimating the burden of COPD in men and women, however, only a few studies have estimated the prevalence of COPD in women aged more than 40 years. Women are equally susceptible to COPD, as they are exposed more to domestic smoke, but they are often neglected and the disease goes unnoticed, which makes them more vulnerable to respiratory failure following a respiratory infection. To gain a comprehensive understanding, this review explores the existing research through a narrative analysis of primary research articles retrieved from PubMed. In total 15 relevant papers were extracted and reviewed. The review finds significant differences exist in the prevalence of COPD among women 40 years of age and older, with greater rates found in rural areas. Women have more severe symptoms and higher fatality rates; contributing factors to this increase are exposure to biomass fuels and growing smoking rates.